Soil Nitrogen Treatment Alters Microbiome Networks Across Farm Niches - Wang, XinYue; Reilly, Kerri; Heathcott, Rosemary; Biswas, Ambarish; Johnson, Linda J.; Teasdale, Suliana; Grelet, Gwen-Aëlle; Podolyan, Anastasija; Gregorini, Pablo; Attwood, Graeme T.; Palevich, Nikola; Morales, Sergio E. (Frontiers in Microbiology, 2022)
Agriculture is fundamental for food production, and microbiomes support agriculture through multiple essential ecosystem services. Despite the importance of individual (i.e. niche specific) agricultural microbiomes, microbiome interactions across niches are not well-understood. To observe the linkages between nearby agricultural microbiomes, multiple approaches (16S, 18S, and ITS) were used to inspect a broad coverage of niche microbiomes. Here we examined agricultural microbiome responses to 3 different nitrogen treatments (0 kg/ha/yr, 150kg/ha/yr and 300kg/ha/yr) in soil and tracked linked responses in other neighbouring farm niches (rumen, faecal, white clover leaf, white clover root, rye grass leaf, rye grass root). Nitrogen treatment had little impact on microbiome structure or composition across niches, but drastically reduced the microbiome network connectivity in soil. Networks of 16S microbiomes were the most sensitive to nitrogen treatment across amplicons, where ITS microbiome networks were the least responsive. Nitrogen enrichment in soil altered soil and the neighbouring microbiome networks, supporting our hypotheses that nitrogen treatment in soil altered microbiomes in soil and in nearby niches. This suggested that agricultural microbiomes across farm niches are ecologically interactive. Therefore, knock-on effects on neighbouring niches should to be considered when management is applied to a single agricultural niche.